Answer:
The recursive rule is a1 = 3 , an = (1/6) a(n-1)
Explanation:
* Lets revise the recursive formula for a geometric sequence:
1. Determine if the sequence is geometric (Do you multiply, or divide,
the same amount from one term to the next?)
2. Find the common ratio. (The number you multiply or divide.)
3. Create a recursive formula by stating the first term, and then
stating the formula to be the common ratio times the
previous term.
# a1 = first term;
# an= r • a(n-1)
- Where:
- a1 = the first term in the sequence
- an = the nth term in the sequence
- an-1 = the term before the nth term
- n = the term number
- r = the common ratio
* Lets solve the problem
∵ an = 3(1/6)^(n-1) ⇒ geometric sequence
∵ The explicit rule is an = a1(r)^n-1
∴ a1 = 3 and r = 1/6
- Lets write the recursive rule
∵ a1 = first term;
∵ an= r • a(n-1)
∴ a1 = 3
∴ an = (1/6) a(n-1)
* The recursive rule is a1 = 3 , an = (1/6) a(n-1)